The Onion and the Mandrake: Plants in Yezidi Folk Beliefs - Arakelova, Victoria (Journal of Persianate studies, 2014)
Abstract The non-dogmatic character of the Yezidi religion presupposes the presence of a heavy layer of so-called “primitive” religious elements, including plant worship. This paper focuses on plants having obvious sacred connotations in Yezidi beliefs, both on the level of the cult and marginal folk beliefs. There is no explicit tree cult in the Yezidism, or dendrolatry, despite the existence of a cultic complex connected with the so-called Dārā mirāzā or “The trees of Desire”. Still, there are representatives of the flora world that bear obvious cultic attribution, the most important of which are the onion and the mandrake. The mandrake has mystical fame and reverence not only among the Yezidis, but also among many other peoples of the region. This panacea for all diseases, widely used in folk medicine, is also considered an important element of the materia magica, primarily due to its aphrodisiac qualities. This paper will provide a comparative analysis of plant worship among the Yezidis and several other traditions of the Caucaso-Iranian region.